Empowering Older Adults in Underserved Communities—An Innovative Approach to Increase Public Health Capacity for Fall Prevention - Subi Gandhi; Laurie Long; Viraj Gandhi; Muna Bashir (Journal of Ageing and Longevity, 2023)
Although evidence-based programs have been effective for fall prevention in many communities, older adults living in underserved areas cannot access these services due to the shortage of providers and trainers. In this cross-sectional study, a multi-agency approach was adopted for integrating an evidence-based program, A Matter of Balance (AMOB), into the public health curriculum at a rurally placed university. We assessed student learning as well as the community benefits of fall prevention among those who participated in the AMOB program. Eighty-four percent of the students reported intentions of using AMOB training in their future careers. The average of the items for the effectiveness of “Classroom Training” and “Community Training” provided by the students (n = 25) ranged from 3.52 to 4.32 and 3.48 to 4.36, on a Likert scale (1 = Strongly Disagree to 5 = Strongly Agree), respectively. Older adults who participated in the fall prevention community workshops showed increased confidence in reducing falls, protecting themselves from falling, and becoming steadier on their feet after the training (p < 0.05). Our study demonstrates the value of integrating evidence-based programs such as AMOB in a university curriculum to address rural health disparities related to falls.